Letalidad hospitalaria por enfermedad cerebrovascular en la provincia de Cienfuegos - Ada Sánchez Lozano; Ada Lozano Leblanc; Joan Rojas Fuentes; Yaineli Cutiño Mass; Ricardo Verdecia Fraga; Ernesto Julio Bernal Valladares (Universidad de las Ciencias Médicas de Cienfuegos, 2014)
Background: cerebrovascular disease is the second leading cause of death in some countries, causing 10 million annual deaths. In-hospital mortality from these diseases is high in our country. Objective: to describe mortality from cerebrovascular disease at the Dr. Gustavo Aldereguía Lima University General Hospital in Cienfuegos during 2006-2010. Methods: a retrospective case series study involving all patients (4449) diagnosed with cerebrovascular disease discharged from the Dr. Gustavo Aldereguía Lima University General Hospital from January 1st, 2006 to December 31, 2010 was conducted. The variables analyzed included age, sex, status at discharge, types of cerebrovascular disease and hospital stay. Results: in-hospital mortality from cerebrovascular disease in the study period was 23.8 %. It was higher in men than in women (24.5 % and 22.9 %, respectively). According to the type of cerebrovascular disease, mortality rate of ischemic stroke was 20 %, subarachnoid hemorrhage, 22.4 % and intraparenchymal hemorrhage, 71.2 %. Conclusions: in-hospital mortality from cerebrovascular disease in Cienfuegos shows a downward trend, though it increased in 2010. It was more common in men. Death from stroke tends to decrease and, to a lesser extent, mortality due to brain hemorrhage, which remains high. There is also an increase in subarachnoid hemorrhage.